Stunting Prevention Efforts Through Mentoring the Use of the SCATION (Stunting Care Application) for Mothers of Toddlers in the Medan City Community Health Center Work Area - Pangaribuan, Ingka Kristina; Mendrofa, Fery Agusman Motuho; Gunarmi, Gunarmi (Griya Eka Sejahtera, 2025)
Background: Stunting is still one of the main health problems in Indonesia that has an impact on physical growth, cognitive development, and the quality of human resources in the future. The use of digital technology, especially mobile-based health applications, is one of the innovative strategies in supporting stunting prevention efforts. This study aimed to analyze the effect of assistance in the use of SCATION (Stunting Care Application) applications on improving the knowledge, attitudes, and behaviors of mothers under five in stunting prevention.Methods: The study used a quasi-experimental design with a one group pretest-posttest with control group design. The sample amounted to 128 mothers under five who were divided into an intervention group (64 people) and a control group (64 people) using the proportionate simple random sampling technique.Results: Data was collected through knowledge questionnaires, early interventions, digital literacy, and application usage logs, then analyzed using the Chi-Square bivariate test and the differential test (t-test/Wilcoxon). The results showed that assistance in the use of the SCATION application had a significant effect on increasing maternal knowledge about stunting (p < 0.05), changes in stunting prevention attitudes and behaviors, and the sustainability of application use after the intervention period. Mothers with good digital literacy, family support, and adequate internet access were more consistent in using apps and showed better preventive behaviors than the control group.Conclusion: SCATION application assistance has proven to be more effective and efficient than conventional methods in improving stunting prevention efforts in mothers under five. Digital technology-based interventions are worthy of being used as an innovative strategy in supporting the national program to accelerate stunting reduction.